Imipenem Hope and Threat From Carbapenemase Enzyme Producing Multi-Drug Resistant (MDR) Klebsiella Pneumoniae (Medical Forum Monthly, 2020)
Objective: To evaluate the in–vitro efficacy of various antibiotics against Klebsiella pneumoniae by paper disk diffusion method and detection of enzyme carbapenemase of the isolates.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Department of Pathology and Microbiology, Indus Medical College Tando Muhammad Khan, for the period of 9 months from Sep 2018 to June 2019.Materials and Methods: Strains were isolated and preserved in Nutrient agar slope in Beijou bottles, followed by subcultures on blood agar plate. Panel of antimicrobial agents e.g. Imipenem, Aztreonam, Gentamicin, Amikacin, Ceftazidime, ciprofloxacin, Cotrimoxazole, Ceftriaxone, Cefoxitin, Keflex, Piperacillin and Ampicillin were used.Results: 104 (95%) strains were sensitive to Imipenem, 48 (44%) sensitive to Amikacin, 45 (41.2%) to Ciprofloxacin, and 32 (29.32%) sensitive to Cotrimoxazole. While 19 (17.4%) were sensitive to Ceftazidime, 18 (16.5%) to Ceftriaxone, and 21 strains showed Carbapenemase enzyme positive activity.Conclusion: Imipenem and other antimicrobial agents showed increased resistance to the organism. It will not be without risk of treatment failure and adverse impact on cost-effectiveness.